A Metabolic Gene Cluster in the Wheat W1 and the Barley Cer-cqu Loci Determines β-Diketone Biosynthesis and Glaucousness. Issue 6 (25th May 2016) - Hen-Avivi, Shelly; Savin, Orna; Racovita, Radu C.; Lee, Wing-Sham; Adamski, Nikolai M.; Malitsky, Sergey; Almekias-Siegl, Efrat; Levy, Matan; Vautrin, Sonia; Bergès, Hélène; Friedlander, Gilgi; Kartvelishvily, Elena; et al.
Abstract : A metabolic gene cluster underlying the known glaucousness loci W1 in wheat and Cer-cqu in barley establishes a novel molecular pathway for β-diketone wax biosynthesis Abstract: The glaucous appearance of wheat ( Triticum aestivum ) and barley ( Hordeum vulgare ) plants, that is the light bluish-gray look of flag leaf, stem, and spike surfaces, results from deposition of cuticular β-diketone wax on their surfaces; this phenotype is associated with high yield, especially under drought conditions. Despite extensive genetic and biochemical characterization, the molecular genetic basis underlying the biosynthesis of β-diketones remains unclear. Here, we discovered that the wheat W1 locus contains a metabolic gene cluster mediating β-diketone biosynthesis. The cluster comprises genes encoding proteins of several families including type-III polyketide synthases, hydrolases, and cytochrome P450s related to known fatty acid hydroxylases. The cluster region was identified in both genetic and physical maps of glaucous and glossy tetraploid wheat, demonstrating entirely different haplotypes in these accessions. Complementary evidence obtained through gene silencing in planta and heterologous expression in bacteria supports a model for a β-diketone biosynthesis pathway involving members of these three protein families. Mutations in homologous genes were identified in the barley eceriferum mutants defective in β - diketone biosynthesis, demonstrating a gene cluster also in the β - diketone biosynthesis Cer-cqu locus in barley. Hence, our findings open new opportunities to breed major cereal crops for surface features that impact yield and stress response.